2013 Breast Cancer Screening Guidelines and Recommendations. (February 2014) - Farrington, Laura Catherine
Breast cancer is the most common nonskin cancer diagnosed among women in the United States and throughout the world, and the leading cause of cancer deaths. Screening recommendations and guidelines vary depending on the organization. Screening modalities include self breast examination, clinical breast examination, mammography, ultrasound, and magnetic resonance imaging. Screening guidelines vary based on individual risk assessment and age.